Antifungal activity determination for the peptides generated by Lactobacillus plantarum TE10 against Aspergillus flavus in maize seeds - Muhialdin, BJ; Algboory, HL; Kadum, H; Mohammed, NK; Saari, N; Hassan, Z; Hussin, ASM (Elsevier Sci Ltd, 2024)
Indexed by WOS/Scopus/ERA